Struktur Kepribadian Ji Ju Yeon dalam Novel Anak yang Memendam Amarah Karya Lee Kkoch Nim: Kajian Psikologi Sastra Sigmund Freud - Yuliana; Soraya , Artifa; Kurnia Rahman, Anita (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This research describes the personality structure of the main character in the novel "Children who harbor anger" by Lee Kkoch Nim. This research uses a qualitative description method, where the research data is in the form of words, phrases, sentences and utterances related to the personality structure of the main character in the story. The data collection technique is through reading, taking notes and analyzing documents using Sigmund Freud's literary psychology. The results show that the first personality structure, namely the id, is the central personality system. Both egos are psychological aspects of personality that arise from the body's need to maintain a good relationship with the real world. The third is the superego or personality morality, which represents the traditional values and social ideals that define the boundaries between good and evil. Overall, these studies show that the ego aspect of personality dominates every problem faced by the main character.